An investigation into the preferential procurement practices in South Africa: Impacts on the South African construction industry - Baloyi, Miranda (My University, 2013)
The study was conducted to investigate the views of the various construction industry stake-holders on Preferential Procurement practices in the various construction phases; and study the impact of these Preferential Procurement practices on the South African construction industry. Based on the political history of the Republic of South Africa, the use of Preferential Procurement is justified. Preferential Procurement is aimed at bridging the economic gap that exists in the country due to the legacy of the Apartheid regime. The target group for the research report was state personnel in Gauteng Governmental departments and municipalities involved in procurement and tenders for services; the contractors and subcontractors registered with the Gauteng Master Builders Association (GMBA) and the contractors registered with the Construction Industry Development Board (CIDB) The Descriptive Survey method was adopted in the study. This method involves two stages of primary data gathering. Qualitative data was gathered through preliminary interviews and quantitative data through a questionnaire survey. Multi-attribute Analytical method was used to analyse the quantitative data, whilst the test of research hypothesis was done through the Spearman Rank Correlation Analysis. The research study shows that the target group is not in agreement on critical issues surrounding Preferential Procurement. The Government and the construction industry professionals are in disagreement on the benefits of Preferential Procurement on the construction industry. This was found as evidence that Government procurement decision makers and the construction industry professionals should increase their interaction and engagement on the issue of Preferential Procurement.